A LEARNER PERFORMANCE-BASED BEHAVIOR ALGORITHM FOR SOLVING TRAVELLING SALESMAN PROBLEM - SALIH, SHAHAD A.; RASHID, TARIK A. (Journal of Duhok University, 2023)
The traveling salesman problem (TSP), is one of the complex optimization problems. TSP is considered as a non-deterministic polynomial-time hardness (NP) hard problem, since its solution cannot be found in certain polynomial time. In this work, a new metaheuristic optimization algorithm called learner performance-based behavior (LPB) was applied to find a feasible solution for TSP. The LPB algorithm’s operators are based on those of genetic algorithms (crossover and mutation). In addition, the genetic algorithm and particle swarm optimization algorithm were applied to TSP to compare the efficiency of the LPB algorithm with them to solve this problem. The LPB outperformed the generic algorithm and the particle swarm algorithm. For instance, when the number of nodes is 30, the population size is 100, and the number of iterations is 500 within a loop of 30 iterations, the minimum averages were: the LPB (655.1900067), the GA (723.084896), and the PSO (692.6886233).